Adaptation of therapeutic care in vulnerable populations experiencing emergency situations - Ovejas, Patricia (2023)
The COVID-19 emergency brought new questions for mental health and, consequently, major challenges for the clinicalapproach of vulnerable populations. The objective of this research was to analyze the work strategies implemented by thePsychological Guidance Center located in the Padre Ricciardelli neighborhood of the City of Buenos Aires to guarantee thecontinuity of therapeutic care during the pandemic. Method: Semi-structured virtual interviews were administered to theworking team professionals and the analysis of the clinical records of patients who consulted during this period was carriedout accordingly. Results: From the coding material process, a central category called adaptation strategies was identified andassociated with seven other study categories: the exercise of leadership as a condition for the development of adaptationstrategies; the need of interdisciplinary work to respond to the emergency; the need to recognize and implement personalresources in the face of the new challenge; the importance of the therapeutic link as a condition to address new foci; thefundamental role of Logotherapy to promote the search for meaning and the inevitable use of technological tools. Conclusion:The present investigation demonstrated the effective implementation of innovative resources, together with already provenstrategies, to guarantee the continuity of therapeutic treatments providing the individual and community psychological supportthat the health emergency demanded in socioeconomically vulnerable populations.